Hematological profile of blood parasitic infected dogs in Southern Thailand - Sorawat Thongsahuan; Usa Chethanond; Siriwat Wasiksiri; Vannarat Saechan; Wichaya Thongtako; Tipayaratn Musikacharoen (Veterinary World, 2020)
Background and Aim: Tick-borne pathogens such as Babesia canis, Hepatozoon canis, and Ehrlichia canis can cause serious disease in canines. Each blood parasite can be associated with different hematological characteristics in infected dogs. Identification of hematological alterations during routine laboratory screening of blood samples from dogs displaying clinical signs is essential for diagnosing blood parasitic infections. This study aimed to evaluate parasitic infections and hematological alterations in blood samples of infected dogs in Southern Thailand.